The Effect of Project Based Learning (PJBL) Learning Model Assisted with Animated Video on Students' Creative Thinking Abilities and Science Processing Skills in Reaction Rate Materials - Anna Juniar; Nurul Fajirah (South Sulawesi Education Development (SSED), 2024)
The research aims to: (1) To determine the influence of the Project Based Learning (PjBL) learning model assisted by animated videos on the ability to think creatively on reaction rate material. (2) To find out whether there is a correlation between students' creative thinking abilities and science process skills taught using the Project Based Learning (PjBL) learning model assisted by animation videos on reaction rate material. The population in this study were all class XI students of SMAN 10 Medan. Sample selection was carried out using purposive sampling, namely XI IPA 3 and XI IPA 1. The instruments used were an essay test on creative thinking skills with 12 valid questions and an observation sheet on science process skills. The research results showed that there was a difference in the average value of creative thinking ability in the experimental class of 83.06, which was greater than in the control class of 73.11. From the right-sided t-test with a significance level = 0.05, the t count is 8.706 and the t table is 1.668. Then, in the correlation test between creative thinking abilities and scientific process skills, a correlation coefficient value of 0.661 was obtained in the high category.